Deterministic and Probabilistic Approaches for Estimating Oil Reserve in Carbonate Reservoir: A Case Study for the Buzrgan Oil Field, Southern Iraq (Journal of Engineering, 2026)
The accuracy in oil reserve estimation is very important, as decisions should be made based on this value. The present paper will deal with estimating oil reserves by using deterministic and probabilistic approaches. The case study is the Mishrif formation of the Buzrgan oil field that located in Missan Governorate, southern Iraq. The deterministic approach is represented by the material balance equation, while the probabilistic approach is represented by Monte Carlo simulation. The data used in the material balance equation are production, PVT, and pressure data, along with needing to calculate bulk volume and porosity, while the Monte Carlo simulation needs volumetric equation parameters, which are porosity, fluid saturation, net pay thickness, and reservoir bulk volume. The linearized material balance equation, the Havlena – Odah method, is used. Monte Carlo simulation is applied as a volumetric equation, but each input parameter is modeled to get the best value. The result of the oil reserve by the material balance equation was 4.368 billion stock tank barrel while by Monte Carlo simulation was classified by Hefner and Thompson’s classification as P90 proven reserves is 1.03279 billion stock tank barrel, proved and probable oil reserves P50 is 1.98761 billion stock tank barrel, and proved, probable, and possibly reserve P10 is 4.3694 billion stock tank barrel. The material balance equation cannot be used before the production stage, while the Monte Carlo simulation can be applied before that.